Heterodimetallic Ferrocenyl Dithiophosphonate Complexes of Nickel(II), Zinc(II) and Cadmium(II) as Sensitizers for TiO2‐Based Dye‐Sensitized Solar Cells. Issue 25 (1st July 2019) - Ajayi, Tomilola J.; Ollengo, Moses; le Roux, Lukas; Pillay, Michael N.; Staples, Richard J.; Biros, Shannon M.; Wenderich, Kasper; Mei, Bastian; van Zyl, Werner E.
Abstract: The formation, characterization, and dye sensitized solar cell application of nickel(II), zinc(II) and cadmium(II) ferrocenyl dithiophosphonate complexes were investigated. The multidentate monoanionic ligand [S2 PFc(OH)] − (L1 ) was synthesized. The reaction between metal salt precursors and L1 produced Ni(II) complexes of the type [NiS2 P(Fc)(OH)2 ] (1 ) (molar ratio 1:2), and a tetranickel(II) complex of the type [Ni2 S2 OP(Fc)2 ]2 (2 ) (molar ratio (1:1). It also produced a Zn(II) complex [ZnS2 P(Fc)(OH)2 ]2 (3 ), and a Cd(II) complex [CdS2 P(Fc)(OH)2 ]2 (4 ). Complexes 1–4 were characterized by 1 H and 31 P NMR, FTIR and elemental analysis, and complexes 1 and 2 were additionally analyzed by X‐ray crystallography. The first examples of dye‐sensitized solar cells (DSSCs) co‐sensitized with ferrocenyl dithiophosphonate complexes 1–4 are reported. Co‐sensitization with the ruthenium dye N719, produced the dye materials (3 )‐N719 (η=8.30%) and (4 )‐N719 (η=7.78%), and they were found to have a better overall conversion efficiency than the pure Ru N719 dye standard (η=7.14%) under the same experimental conditions. The DSSCs were characterized using UV/vis, cyclic voltammetry, electrochemical impedance spectroscopy (EIS), photovoltaic‐ (I−V curves), and performing incident photon‐to‐current efficiency (IPCE) measurements. Abstract : Formation, structure, electrochemistry, photo‐chemistry and ‐physics of new nickel(II), zinc(II) and cadmium(II) ferrocenyl dithiophosphonate complexes were investigated as sensitizers for dye‐sensitized solar cells (DSSC). Co‐sensitization produced dye materials with a better overall conversion efficiency than pure N719 dye standard.